2007
DOI: 10.1111/j.1532-849x.2007.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Adaptation and Color Stability of Four Provisional Materials

Abstract: Provisional crowns fabricated from SNAP, Protemp Garant, and Integrity exhibited similarly low marginal discrepancy. SNAP, Luxatemp Solar, and Integrity did not demonstrate a clinically detectable change in shade after 1 week in a staining solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 18 publications
5
60
1
10
Order By: Relevance
“…These results corroborate the findings of previous studies that evaluated the color stability of different materials and observed that Protemp resin also presented high color change values 2,16 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results corroborate the findings of previous studies that evaluated the color stability of different materials and observed that Protemp resin also presented high color change values 2,16 .…”
Section: Discussionsupporting
confidence: 92%
“…Guaranteeing the color stability of temporary restorative materials is an essential factor with great influence on the success of prosthetic rehabilitations, considering that during the stage of temporary restorations, patients concentrate their concern on the function and esthetics of the restorations 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Long-term interim FDPs require materials that have color stability and mechanical properties that ensure adequate fracture strength and sufficient dimensional and marginal stability. [2][3][4][5] Polyethyl and polymethyl methacrylates (PEMA and PMMAs) are conventional chairside materials used in direct and indirect restorative procedures. Bis-acryl, based on multifunctional methacrylic acid esters, has similar properties to those of conventional materials and is also used in the direct technique.…”
mentioning
confidence: 99%
“…IDS was intended to provide advantages such as protection from infiltration and bacterial leakage during the provisional restoration stage, reduction of potential risk for postcementation sensitivity, minimization of anesthesia required during cementation of the definitive restoration, and improved bond strength to the tooth structure [6], as well as addressing the primary problem of reduced shear bond strength associated with provisional treatment. A key element in IDS is the development of an effective bond between the existing resin coating and the new luting composite resin [7], considering that bond strength could start to decreased after 7 days after IDS procedure [20].…”
Section: Resultsmentioning
confidence: 99%